A Study on Factors Affecting the Interest of People Buying Tablet in Klang Valley - Phang, Juinn Zhi (2014)
This study aim to examine the structural relationship between social influence, brand name, functionality, complexity, and cost level with tablet buying decision in Klang Valley. 385 respondents are selected randomly to answer the questionnaires, questionnaires consists of Section A, which designed as nominal scale, and Section B are designed as five point likert scale. SPSS and Smart PLS are employed to test the significant of the result. Study show that brand name is the strongest factor that affecting people buying tablet in Klang Valley. This study contributes significantly to government, corporation (manufacturer) as well as individual researcher. This study especially contribute to manufacturer who should emphasize on their brand name in advertising as to be well positioned in consumers’ mind when consumer making the decision to purchase and own a tablet. This study provides valuable insight regarding consumer guying behavior toward tablet which is not much cover in Malaysia’s literature. The lesson can also be applied in other countries for marketing tablet.